Individual and Social Model of Intellectual Disability in Teachers’ and Students’ Beliefs - Parchomiuk, Monika (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Author’s research discussed in the following article was aimed at determining which model of intellectual disability is preferred by teachers and students, and what the differences are between these respondents in this respect. The assumptions characteristic for the individual model focused on the person with disability, and in particular, on his or her biological (physical) defects. The defects that caused limitations in functioning were treated as the basis of disability. Professional activities (mostly medical) focused on adjusting to the state of limited functioning, seen in a reductionist way: as accepting the loss of ability or independence. The social model situated the origin of disability in society. In this perspective, it defined disability as the product of specific social and economic structures, and its main interest focused on the problems of oppression and discrimination of persons with disability. Research was carried out with special needs teachers who work with individuals with intellectual disability, teachers working with able-bodied individuals, and students of special pedagogy. The Likert type scale, called “The model of an intellectual disability”, was used to determine the model of intellectual disability. The research had a cognitive goal but also a significant practical goal related to the specialists’ professional training. The article offers general recommendations for shaping attitudes and assessments connected with noticing possibilities in the lives of individuals with intellectual disability, taking into account the influence of environmental factors.